Analisis Perbandingan Kinerja Keuangan PT Bank Syariah Mandiri Dengan Menggunakan Pendekatan Laba Rugi Dan Nilai Tambah Periode Tahun 2016-2020 - Nuri Fitriani; Ratih Puspitasari (Jurnal Ilmiah Akuntansi Kesatuan, 2021)
The analysis of the financial performance of Islamic banks so far has been carried out only based on the balance sheet and income statements, not using the value added report as recommended by Baydoun and Willet (2000), an expert in Islamic accounting. The purpose of this research is to review the financial performance of Islamic banking by comparing the results of financial performance using the profit and loss approach and those using added value. To obtain accurate evidence regarding differences in the financial performance of Islamic banking when calculated using the profit and loss approach and added value, it is seen from the ratio of ROA, ROE, LBAP, NPM and BOPO. This study took a sample on the financial statements of PT. Bank Syariah Mandiri 2016 to 2020. Keywords: Financial Performance, Income Statement, Value Added Report